ANALISA PENDAPATAN NELAYAN DI DISTRIK KEPULAUAN AYAU KABUPATEN RAJA AMPAT - , Orpa Gertruida Syaranamual, Ir., Dr. Soeranto, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Fishery resource has high economic value at both big and small scale and can improve fishermenâs prosperity. However, the fact is that many fishermen have not been able to increase their fish catching result that their income remains low. The study aims at observing and analyzing the factors that influence the income of the fishermen who are grouper fish catchers in the District of Ayau Island using Ordinary Least Square (OLS) sampling method. The influencing factors are the number of grouper fish catching days, the quantity of fuel, labor and age. The results of the study show that the number of grouper fish catching days, the quantity of fuel, labor and age collectively influence the income of the fishermen in the District of Ayau Island. The analysis results indicate that the number of the grouper fish catching results significantly influences the income of the fishermen and hence they tend to pay more attention to the quantity of the fuel because it supports the effort to increase the grouper fish catching results. Considering the results of the study it is recommended for the local government to secure the availability of the fuel in the District of Ayau Island at relative low price and also to establish a fishermen cooperative. Additionally, it is necessary for the local government to organize a capacity building and development of the fishermen in catching fishes.